Prevalence of polypharmacy and drug interactions in geriatric patients: A cross-sectional study from India - Umaima Farheen Khaiser; Rokeya Sultana; Ranajit Das; Saeed G. Alzahrani; Madhumitha Kannan; Mohammed Khairt Newigy; Mohammed Sharique Ahmed Quadri; Mujeeb Ahmed Shaikh; Farha M. Shaikh; Mohammad Fareed (PLoS ONE, 2026)
Background Polypharmacy and potential drug-drug interactions (pDDIs) are major challenges in the management of elderly patients with multiple comorbidities, often leading to adverse drug events and increased healthcare burden. Aim This study aimed to determine the prevalence and patterns of polypharmacy and pDDIs among elderly patients attending Yenepoya Medical College and Hospital, Mangalore, India. Methods A cross-sectional study was conducted from January to June 2023 among 310 elderly patients (aged ≥60 years) selected through simple random sampling from both in-patient and out-patient departments. Polypharmacy was defined as the concurrent use of ≥5 medications, and excessive polypharmacy as ≥9 medications. Drug interaction screening was performed using UpToDate and Medscape interaction checker tools. Statistical analyses included descriptive statistics, t-tests, chi-square tests, and regression analysis, with significance set at p < 0.05. Results The prevalence of polypharmacy was slightly higher in females (53.84%) than males (51.94%), with the highest rates observed in the 70–79 age group (48.88%). Most patients experienced moderate (50%) drug interactions. A significant gender difference was observed in the number of drugs prescribed at treatment ( p = 0.0032), but not at discharge. Regression analysis identified gender ( p = 0.018) and inpatient status ( p < 0.001) as significant predictors of polypharmacy, while age was not ( p = 0.719). Conclusion This study reveals a high prevalence of polypharmacy among elderly patients attending Yenepoya Medical College and Hospital. Polypharmacy was found to be more prevalent among female patients, older age groups, and in inpatient wards. The distribution of drug interactions revealed a pervasive nature across various degrees, with moderate interactions being the most common. Future research should use larger samples, and diverse populations to better understand polypharmacy, drug interactions, and outcomes.